Adjuvant systemic therapy in older women with breast cancer - Leone J (Dove Medical Press, 2016)
Julieta Leone,1 Bernardo Amadeo Leone,1 José Pablo Leone2 1Department of Medical Oncology, Grupo Oncológico Cooperativo del Sur (GOCS), Neuquén, Argentina; 2Department of Internal Medicine, Division of Hematology-Oncology and Blood & Marrow Transplantation, University of Iowa Holden Comprehensive Cancer Center, Iowa City, IA, USA Abstract: Breast cancer in the elderly is an increasing clinical problem. In addition, ~60% of deaths from breast cancer occur in women aged 65 years and older. Despite this, older women with breast cancer have been underrepresented in clinical trials, and this has led to less than optimal evidence to guide their therapy. The management of elderly women with early breast cancer is a complex process that requires careful evaluation of life expectancy, comorbidities, patient values, and risks and benefits of available treatment options. This review will focus on current adjuvant systemic therapy options for older women with breast cancer, discuss the principles in the decision-making process, and define the role of endocrine therapy, chemotherapy, and targeted agents. Keywords: breast cancer, adjuvant therapy, chemotherapy, endocrine therapy, elderly